Pembentukan Karakter Anak Melalui Komunikasi Interpersonal dan Keteladanan Orangtua pada Kelas Vi Sdi Al-Achfas Dwi Matra Jakarta - Hunainah Hunainah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The aim of the research is to find out children’s character development through interpersonal communication and parents’ role model in Islamic Elementary School Al-Achfas Dwi Matra South Jakarta. This research is conducted by using Descriptive method. The data is collected through observation, interview, and documentation, and then it is analyzed descriptively by several steps such as data reduction, data presentation and deduction. Parents with good interpersonal communication are the source of children’s physical and spiritual health. Therefore, a child who is educated communicatively with good role model will grow as a mature human being who is physically and spiritually healthy. A good role model is an effective method to teach moral values to children due to their character as imitators. The result of this research shows that parents in Islamic Elementary School Al-Achfas Dwi Matra Jakarta are able to provide interpersonal communication and good role model in children’s character development.